Strategi Percepatan Penurunan Angka Stunting Melalui Pendampingan Terpadu di Kelurahan Kademangan Kota Probolinggo - Wahyono, Eko; Supriyanto, Supriyanto; Mubaroq, Husni; Fadilah, Siti Nur; Bahiyah, Khoridatil; Fryo, Mohammad (Abdimas Universal, 2025)
Kademangan District, Probolinggo City, East Java has a fairly high stunting rate, reaching 33.4% in 2020. This condition is caused by various factors, such as poverty, less than optimal parenting practices, and limited access to health services. To accelerate the reduction in stunting rates in this area, the Probolinggo City government has implemented various interventions, including programs providing additional food,nutrition education, and increasing access to health services. However, more comprehensive and sustainable efforts are still needed to address the problem of stunting effectively.  This community service aims to increase the knowledge and skills of the community in Kademangan District in implementing good parenting and nutritional practices to prevent stunting in children. The methods used include counseling, providing additional food, as well as ongoing assistance and monitoring. The results of the activity show an increase in mothers' knowledge and practice in feeding, health care and stimulating children's growth and development. Apart from that, there has been a decrease in the prevalence of stunting in the target areas. It is hoped that this effort can become a model for comprehensive and sustainable stunting interventions in the future.